Poem ich setzte den Fuß in die Luft und sie trug (Hilde Domin) - Schmerberg, Ralf 1965-; Lustig, Franz 1967-; Haas, Susanne; Becker, Meret 1969-; Rainer, Luise 1910-2014; Brandauer, Klaus Maria 1943-; Celan, Paul 1920-1970; Elsner, Hannelore 1942-2019; Beckmann, Jorinde (Trigger Happy Productions, 2004)
Visual interpretations of a collection of poetry.
Bildformat: DVD 1: 16:9. - DVD 2: 4:3
Orig.: Deutschland, USA 2003
Enth. "Behind Poem" (56 Min.)
Keywords: Experimental